Peningkatan Pengetahuan Melalui Penyuluhan Manfaat Seduhan Jahe Emprit Terhadap Penanganan Mual Muntah Ibu Hamil Trimester I - Ani T Prianti; Sutrani Syarif; Nurhidayat Triananingsih; Nurul Fitri Sugiarti Syam (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Pregnancy affects the body of pregnant women by causing physiological changes that occur throughout the organ system, most of the changes in the body of pregnant women are caused by hormonal work. These changes occur due to the imbalance of progestrogen and estrogen hormones in the body of pregnant women. As many as 50% of pregnant women experience emesis gravidarum, known as morning sickness. Emesis gravidarum causes a decrease in appetite, so there is a change in electrolyte balance with potassium, calcium, and sodium which causes changes in body metabolism. Ginger Warming in Reducing the Frequency of Nausea and Vomiting in Trimester I Pregnant Women, said that before being given the intervention, the average respondent experienced the frequency of nausea and vomiting as much as 13 times a day, after being given a warm ginger drink intervention, the average frequency of nausea and vomiting decreased to 3.18 times a day. Ginger is efficacious as anti-vomiting and can be used by pregnant women to reduce morning sickness.Research shows that ginger is very effective in reducing metoclopamid, a compound that induces nausea and vomiting (Hasanah, 2014).The first advantage of ginger is the content of essential oils that have a refreshing effect and block the gag reflex, while gingerol can launch blood and nerves work well. As a result, tension can be melted, the head becomes fresh, and nausea and vomiting are suppressed. The fragrant aroma of ginger is produced by volatile oil. Ginger can prevent nausea and vomiting because ginger can be a barrier to serotonin. Ginger is effective in reducing nausea and vomiting during first trimester pregnancy.